2005
DOI: 10.1007/s11325-005-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of an oral appliance in the treatment of obstructive sleep apnea syndrome

Abstract: The purpose of this study was to investigate the effects of an oral appliance (OA), with and without mandible advance, in the treatment of obstructive sleep apnea syndrome (OSA). Twenty-four patients diagnosed with OSA agreed to participate in this study. The patients were treated for 3 months (with a removable soft elastic silicone positioner customized with thermoplastic silicone and with a 5-mm opening). Patients were selected, using a randomized design, to receive an OA model either with (12 patients) or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 38 publications
4
116
2
14
Order By: Relevance
“…The RCTs evaluated the effects of MADs compared with placebo treatment [11,13,14,22,23,25,[28][29][30], CPAP [11, 13, 16-19, 24, 26, 32, 34] or between appliance designs [15,20,27,31,33,35,36,38]. Three studies reported longer-term results from MAD treatment after 1-4 yrs, compared with CPAP [12], surgery [37] or between two types of MAD [21].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…The RCTs evaluated the effects of MADs compared with placebo treatment [11,13,14,22,23,25,[28][29][30], CPAP [11, 13, 16-19, 24, 26, 32, 34] or between appliance designs [15,20,27,31,33,35,36,38]. Three studies reported longer-term results from MAD treatment after 1-4 yrs, compared with CPAP [12], surgery [37] or between two types of MAD [21].…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…In addition, adjustable OAs can also be expensive, with fees for fabricating and adjusting these devices potentially exceeding $3000, 22 causing adjustable OAs in some settings to be more expensive than CPAP. 24 In addition to the time required to fabricate adjustable OAs, a period of incremental titration is needed to facilitate patients› tolerance of the mandibular advancement, which further adds to the inherent delay to effective treatment.…”
Section: Oral Appliancesmentioning
confidence: 99%
“…Fixed OAs have been shown to reduce events, but their ability to provide adequate therapy or normalize the AHI has not been established. [24][25][26] No large studies directly comparing the performance between fixed and adjustable OAs have been conducted. While fixed OAs offer advantages, they may not provide adequate reduction of obstructive respiratory events and may result in residual disease or inadequate therapy for some patients.…”
Section: Oral Appliancesmentioning
confidence: 99%
“…(19) publicaron resultados favorables con ambos dispositivos (protrusión 0% y protrusión 75%) respecto de la permeabilidad de la vía aérea Rev. Clin.…”
Section: Discussionunclassified